Evaluation of antioxidant potential, identification of constituents and storage stability of Artocarpus heterophyllus J33 variety fruit waste extract / Mohd Nazrul Hisham Daud - Daud, Mohd Nazrul Hisham (Institute of Graduate Studies, UiTM, 2018)
Artocarpus heterophyllus J33 (AhJ33) is an important fruit variety among A. heterophyllus in Malaysia and widely cultivated. For market purposes, the pulp is usually separated from the skin, which is usually discarded. Towards the conversion of AhJ33 fruit waste to a food product of high antioxidant potential, the specific objectives of this study were to evaluate the effect of three extraction methods on the antioxidant activity of AhJ33 fruit skin, isolate and identify the major and minor antioxidant constituents of the most active extract and evaluate its stability at three storage conditions. The fruit skin including rind and rachis were separated, dried, ground and extracted via maceration, percolation and Soxhlet techniques with 70% aqueous ethanol. Antioxidant activities were evaluated by DPPH, FRAP and b-carotene assays and correlated to their phenolic and polyphenols contents which are estimated by TPC and TFC assays, respectively. The bioassay-guided isolation and identification of the major antioxidant constituents involved liquid-liquid partitioning (LLP) of the most active extract into ethyl acetate (EtOAc), dichloromethane (DCM) and aqueous (AQ) fractions followed by isolation and characterization of pure compounds via chromatographic and spectroscopic techniques, respectively. Minor antioxidant constituents of active extract were identified by TOF LCMS analyses based on total ion chromatograms (TIC) and LC-UV profiles at X 254, 280 and 310 nm assisted mostly by built-in and online databases. The stability of stored extracts was evaluated by DPPH inhibition as well as qualitative and quantitative analyses of their major antioxidant constituents by LCMS and HPLC, respectively, throughout a period of 0-6 months…